2007
DOI: 10.1074/jbc.m607949200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Spectroscopic Characterization of P450 BM3 Mutants with Unprecedented P450 Heme Iron Ligand Sets

Abstract: Two novel P450 heme iron ligand sets were generated by directed mutagenesis of the flavocytochrome P450 BM3 heme domain. The A264H and A264K variants produce CysFe-His and Cys-Fe-Lys axial ligand sets, which were validated structurally and characterized by spectroscopic analysis. EPR and magnetic circular dichroism (MCD) provided fingerprints defining these P450 ligand sets. Near IR MCD spectra identified ferric low spin charge-transfer bands diagnostic of the novel ligands. For the A264K mutant, this is the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 41 publications
9
80
0
1
Order By: Relevance
“…[19,26,27] When the C a atoms are superposed onto those of substrate-free WT (PDB ID: 1BU7), [28] the root mean square deviation (rmsd) for the 271 "structurally invariant" residues, as defined by Haines et al, [17] is 0.32 . As in other P450 BM3 structures, [15,29] the porphyrin system is found to incorporate in either of two orientations related by a 1808 rotation ( Figure S1 in the Supporting Information). The important SRS5 substrate recognition region, [30][31][32] to which Ala330 and Pro329 belong, is dramatically reshaped.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…[19,26,27] When the C a atoms are superposed onto those of substrate-free WT (PDB ID: 1BU7), [28] the root mean square deviation (rmsd) for the 271 "structurally invariant" residues, as defined by Haines et al, [17] is 0.32 . As in other P450 BM3 structures, [15,29] the porphyrin system is found to incorporate in either of two orientations related by a 1808 rotation ( Figure S1 in the Supporting Information). The important SRS5 substrate recognition region, [30][31][32] to which Ala330 and Pro329 belong, is dramatically reshaped.…”
Section: Resultssupporting
confidence: 71%
“…[3,4] Compound types successfully targeted include polycyclic aromatic hydrocarbons and other environmental contaminants, [5] short-chain alkanes, [6] sugars, [7] terpenoids [8,9] and medicinal compounds. [10][11][12] Crystal structures are available for the substrate-free (SF) haem domain of the wild-type (WT) enzyme, [13][14][15] various substrate-bound (SB) complexes, [16,17] and several variants, [6,[18][19][20][21] including I401E. [22] Because none of the SB structures depicts a substrate in a "productive" conformation (i.e., with a CÀH bond close to the haem iron), the roles of several active-site residues have yet to be fully clarified, and the manner in which mutations impact substrate binding, activity and selectivity is not always self-evident.…”
Section: Introductionmentioning
confidence: 99%
“…However, the WT BM3 heme domain occupies a distinct conformation when SF, and thus the A82F mutation is key to shifting the equilibrium between SF and SB conformations. Previous studies also showed that the structural state of the heme domain can be significantly affected by single mutations at key positions (36).…”
Section: Characterization Of Omeprazole Binding Properties Of Bm3mentioning
confidence: 97%
“…This peculiar homodimeric state is also observed in solution by UV-visible spectroscopy with the Soret maximum at 424 nm. Another example is an engineered A264H mutant of P450 BM3 (9). Ala264 residue is located in the I helix and close to the heme iron, and mutation at this residue creates an unusual ligand set at the sixth position, e.g., glutamate (15), lysine, or histidine (9).…”
Section: Resultsmentioning
confidence: 99%
“…Another example is an engineered A264H mutant of P450 BM3 (9). Ala264 residue is located in the I helix and close to the heme iron, and mutation at this residue creates an unusual ligand set at the sixth position, e.g., glutamate (15), lysine, or histidine (9). The coordinated state is stable in solution and has been clearly characterized by spectroscopic methods, including UV-visible absorption spectra (Soret maximum at 427 nm), EPR (g ϭ 2.50, 2.26, and 1.89) and magnetic circular dichroism.…”
Section: Resultsmentioning
confidence: 99%